Analytic Review of Dissertations Defended on Specialty 14.01.10 - «Pediatrics» in Specialized Scientific Board D 08.601.02 - L.R. Shostakovych-Koretska; V.V. Mavrutenkov; A.V. Cherginets (Zaslavsky O.Yu., 2014)
The work presents results of dissertations analysis on specialty «pediatrics» defended in specialized scientific board В 08.601.02 during 2004-2013.